Audit Aplication of Premium Quality Information System Using Audit Through the Computer Method - Fatullah, Fajri; Auliana, Sigit; Permana, Basuki Rakhim Setya; Mansyuri, Umar; Hamdan, Hamdan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
Information system audits are carried out to determine the extent of information system management in the company whether it is in accordance with established procedures and standards or not. Information systems aim to expedite every job. The purpose and objective of this study is to assess and evaluate internal control over information systems that run in a company and correct whether according to predetermined procedures and standards. The method used in collecting information is done by interviewing, observing and distributing questionnaires to system users. The method used is Audit Through the Computer. Then it can be seen the results of the Premium Quality Information (PQI) information system audit at Factory 5 PT. Parkland World Indonesia on the right Information System Audit recommendations through the analysis used are good and sufficient in supporting the achievement of the vision and mission of a company properly and the production of strategic solutions in order to solve the various problems faced. The results of this study found that the system used has not met the needs of the company, there are still obstacles that make the system not used.